2006
DOI: 10.3141/1960-12
|View full text |Cite
|
Sign up to set email alerts
|

So You Want to Make a High-Occupancy Toll Lane?: Project Manager's Guide for Conversion from High-Occupancy Vehicle Lane to High-Occupancy Toll Lane

Abstract: Although high-occupancy toll (HOT) lanes have been studied or have existed for more than 10 years, the continuing developmental nature of these concepts means that there is little guidance for project managers on how to manage the process of converting a high-occupancy vehicle (HOV) lane to a HOT lane. Many guidelines have been published about the technical elements of HOT lane development and operations. A project manager of an HOV to HOT lane conversion process would face issues that differ from those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The following conditions must be satisfied to avoid adverse effects. Dahlgren (2002) and Ungemah, Swisher (2006) showed that (1) recurring congestion in the GP lanes and (2) unused capacity in the HOV lane are two necessary conditions that ensure successful implementation of a HOT lane. To check these conditions, we analysed 30-sec, aggregated traffic data that were collected via inductive loop detectors installed on the expressway.…”
Section: Necessary Conditions For Implementing Hot Lanementioning
confidence: 98%
“…The following conditions must be satisfied to avoid adverse effects. Dahlgren (2002) and Ungemah, Swisher (2006) showed that (1) recurring congestion in the GP lanes and (2) unused capacity in the HOV lane are two necessary conditions that ensure successful implementation of a HOT lane. To check these conditions, we analysed 30-sec, aggregated traffic data that were collected via inductive loop detectors installed on the expressway.…”
Section: Necessary Conditions For Implementing Hot Lanementioning
confidence: 98%
“…Transportation professionals, including planners, engineers, and economists, are often interested in tolling and pricing as they relate to overall system management, peak-period trip reduction, and revenue generation. Although there is a temptation to view tolls as a silverbullet solution, tolling should be proposed in the context of other elements of an overall regional transportation strategy, including land use regulations, transportation demand management strategies, intelligent transportation systems technologies, and transit (19).…”
Section: Transportation Professionalsmentioning
confidence: 99%
“…HOT lanes have existed for many years but there are no set standards or guidelines for engineers, planners and project managers regarding how to implement, operate and maintain such 37 facilities. A study by Ungemah et al (2006) Stated preference surveys are commonly used for proposed facilities and revealed 38 preference surveys for existing facilities. Public opinion is often an important factor when deciding whether or not to build a new transportation facility and how to operate it, so some studies consider public opinion.…”
Section: Previous Researchmentioning
confidence: 99%